A Local View of Facility Siting - Meagher, Don (Maine Policy Review, 1992)
The seeming paralysis in siting waste disposal facilities and other new facilities in Maine and other states underscores the difficulty of designing and implementing processes that will safeguard the environment and human health while sustaining economic development Don Meagher of the Eastern Maine Development Corporation describes the lessons learned from his involvement in an effort to site a demolition debris facility.